2014
DOI: 10.1371/journal.pone.0096365
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Interplay between ERK1/2, TGFβ/Smad, and Jagged/Notch Signaling Pathways in the Regulation of Epithelial-Mesenchymal Transition in Retinal Pigment Epithelium Cells

Abstract: Epithelial-mesenchymal transition (EMT) of retinal pigment epithelium (RPE) cells is a major pathologic change in the development of proliferative vitreoretinopathy (PVR), which leads to severe visual impairment. ERK1/2 pathway has been reported to play a key role in the carcinogenesis, cancer metastasis, and multiple fibrotic diseases. We hypothesized that ERK1/2 signaling could cross-interact with transforming growth factor β2 (TGFβ2)/Smad and Notch signaling pathways in the regulation of EMT in RPE cells. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
3
37
0
Order By: Relevance
“…In the posterior eye, they are the likely causative factor behind the EMT of the RPE, a process that includes marked structural and functional alterations such as loss of the outer blood-retina barrier, reduced expression of RPE-characteristic genes, upregulation of αSMA and change from a cuboidal to a more spindle-shaped phenotype. Quite comparable changes as observed here in vivo have been reported for TGF-β-treated cultured RPE cells from various mammalian species (Gamulescu et al 2006;Kurosaka et al 1996;Lee et al 2001;Jun and Joo 2016;Tamiya and Kaplan 2016;Dvashi et al 2015;Yang et al 2016;Chen et al 2014). Overall, there is strong evidence that TGF-β signaling is among the most potent inducers of EMT in numerous epithelial cell types in and outside the eye (Miettinen et al 1994;Saika et al 2004;Roberts et al 2006;Thiery et al 2009;Thiery and Sleeman 2006;Kalluri and Neilson 2003;Guarino et al 2009;Hales et al 1994;Xu et al 2009).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the posterior eye, they are the likely causative factor behind the EMT of the RPE, a process that includes marked structural and functional alterations such as loss of the outer blood-retina barrier, reduced expression of RPE-characteristic genes, upregulation of αSMA and change from a cuboidal to a more spindle-shaped phenotype. Quite comparable changes as observed here in vivo have been reported for TGF-β-treated cultured RPE cells from various mammalian species (Gamulescu et al 2006;Kurosaka et al 1996;Lee et al 2001;Jun and Joo 2016;Tamiya and Kaplan 2016;Dvashi et al 2015;Yang et al 2016;Chen et al 2014). Overall, there is strong evidence that TGF-β signaling is among the most potent inducers of EMT in numerous epithelial cell types in and outside the eye (Miettinen et al 1994;Saika et al 2004;Roberts et al 2006;Thiery et al 2009;Thiery and Sleeman 2006;Kalluri and Neilson 2003;Guarino et al 2009;Hales et al 1994;Xu et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Since in culture conditions transforming growth factor-β (TGF-β) signaling has been reported to be a potent mediator of EMT in RPE cells (Gamulescu et al 2006;Kurosaka et al 1996;Lee et al 2001;Chen et al 2014;Tamiya and Kaplan 2016;Dvashi et al 2015;Jun and Joo 2016;Yang et al 2016), we studied the retinal phenotype of βB1-TGF-β1 mice, a transgenic mouse strain with an ocular overexpression of active TGF-β1 (Flügel-Koch et al 2002). Here, we show that the RPE of βB1-TGF-β1 mice undergoes an EMT, a process that becomes manifest after birth.…”
Section: Introductionmentioning
confidence: 99%
“…Other eye-specific myofibroblast precursors are cells derived from the lamina cribrosa in glaucoma (Kirwan et al, 2005;Wallace et al, 2014) and Müller cells in proliferative diabetic retinopathy (Guidry et al, 2009). EMT is another local source to possibly generate ocular myofibroblasts from human lens epithelial cells (Dawes et al, 2009;Liu et al, 1994;Lovicu et al, 2015;Nishi et al, 1996), retinal pigment epithelial cells (Chen et al, 2014;Parapuram et al, 2009), and corneal epithelial progenitor cells (Kawakita et al, 2005;Kawakita et al, 2013). Special to the eye is the possible M A N U S C R I P T…”
Section: Myofibroblast Precursors Of the Eyementioning
confidence: 99%
“…TGFβ2 activates the p38 MAPK pathway and blockade of this pathway inhibited the expression and synthesis of collagen type I in human RPE cells (Kimoto et al, 2004). Chen et al showed that TGFβ2 induced the activation of ERK1/2 and Jagged/Notch signaling in human RPE cells (Chen et al, 2014b). Inhibition of ERK1/2 signaling using U0126 prevented the progression of EMT in RPE cells by abrogating both the Smad and Jagged/Notch signaling pathways (Chen et al, 2014b).…”
Section: Proliferative Retinal Diseasementioning
confidence: 99%